2021
DOI: 10.1108/ijse-05-2021-0273
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and bridging social capital towards collective action in participatory irrigation management. Evidence in Chiang Rai Province, Northern Thailand

Abstract: PurposeThe purpose of this paper is to examine the effect of social capital with bonding and bridging distinction in promoting higher participation in collective action in participatory irrigation management.Design/methodology/approachA sample of 304 farmers was surveyed using a structured questionnaire. A focus group discussion was also carried out with randomly selected water users, leaders and irrigation officers. A confirmatory factor analysis and structural equation modelling were used to test the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies often found unsuccessful PIM adoption characterized by uncooperative irrigation officers and fragmented water user groups. In comparison, successful PIM demonstrates a high level of social cohesion, perceived trust, shared goals, and strong commitments [ 28 , 30 ]. The joint management of irrigation projects under PIM, requires developing the officers' social skills to work with farmers effectively.…”
Section: Pim Social Capital and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies often found unsuccessful PIM adoption characterized by uncooperative irrigation officers and fragmented water user groups. In comparison, successful PIM demonstrates a high level of social cohesion, perceived trust, shared goals, and strong commitments [ 28 , 30 ]. The joint management of irrigation projects under PIM, requires developing the officers' social skills to work with farmers effectively.…”
Section: Pim Social Capital and Conceptual Frameworkmentioning
confidence: 99%
“…Despite the widespread adoption of Participatory Irrigation Management (PIM) for shared resource management in irrigation projects, as evidenced by its application in countries such as Pakistan, India, and the Philippines, challenges persist in its implementation, including issues with defection, low participation rates, and illegal operation of irrigation infrastructure [ 9 , 26 , 27 ]. While previous studies have explored various factors that may contribute to the successful implementation of PIM, such as conflict resolution [ 28 ], group meetings [ 28 , 29 ], social capital [ 16 , 30 ], human capital [ 31 ], and institutional factors [ 32 ], there remains a gap in the research regarding the interrelationships between PIM, collective irrigation, and their impact on farm production. Therefore, this study fills this gap by examining the direct and indirect effects of the interplay between social capital, PIM implementation, and production efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, AWD adoption involves additional investment, such as additional time required to monitor the field and the irrigation surface. Managing and monitoring irrigation can be complex, given the high cases of deflection in a communal resource [28,29]. Enriquez [14] views AWD adoption as viable to a collective organization such as farmer groups (e.g., cooperatives, GAP farmers) to minimize transaction costs.…”
Section: Innovation Advantages Ease Of Adoption and Trial Capability ...mentioning
confidence: 99%
“…To foster integrity in water governance, social capital can strengthen public participation through building cooperation and raising greater inclusion and cohesion. Some studies have shown that social capital tends to increase stakeholder participation in irrigation management [ 11 , 12 ]. In recent years, the significance of social capital in farmers' participation in water and irrigation management has been well established, especially in developing countries (e.g., Khalkheili and Zamani [ 13 ], Rivera et al [ 14 ], and Zhang et al [ 15 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the significance of social capital in farmers' participation in water and irrigation management has been well established, especially in developing countries (e.g., Khalkheili and Zamani [ 13 ], Rivera et al [ 14 ], and Zhang et al [ 15 ]). Research into the role of social capital in participation in irrigation management in Thailand has been undertaken, but did not focus on a multi-level governance approach [ 12 , 16 ]. Little attention has been paid to the influence of social capital on participation in “multi-level” irrigation management among farmers in the Thai context, where a traditional collective society is dominant.…”
Section: Introductionmentioning
confidence: 99%